Orthotic Bracing or Minimally Invasive Surgery? A Summary of 767 Pectus Carinatum Cases for 9 Years. (19th February 2021) - Shang, Ziyin; Hong, Chun; Duan, Xianlun; Li, Xiangyong; Si, Yuan
Abstract : Orthotic bracing and minimally invasive surgery are currently the treatment methods for pectus carinatum. We present our experience with the advantages, method selection criteria, and precautions for both treatment methods. A total of 767 pediatric patients (596 boys and 171 girls) with pectus carinatum were retrospectively analyzed. All of them received orthotic bracing, and 108 pediatric patients received minimally invasive surgery, achieving good outcomes. Among the 767 pediatric patients, 644 obtained satisfactory chest appearance through orthotic bracing, with a success rate of 84.0%. Younger pediatric patients had better orthotic outcomes. Among the 123 failure cases, 108 pediatric patients underwent minimally invasive surgery as the treatment. Seventy-six pediatric patients with simple chondrogladiolar prominence underwent a minimally invasive sternal depression procedure, whereas 32 pediatric patients with complex chondromanubrial prominence underwent surgery. All 108 pediatric patients successfully completed the surgery. The operation time was 112.8 ± 23.5 min, and the average length of hospital stay after the surgery was 7 days. A follow-up was conducted for at least 3 months and up to 3 years. The orthotic effect was satisfactory. For younger pediatric patients with pectus carinatum, noninvasive orthotic bracing treatment should be considered first. For older pediatric patients, the failure rate of the bracing was higher, and the outcomes were often unsatisfactory. Especially for patients over 15 years old, minimally invasive sternal depression may be the preferred treatment for pectus carinatum.